(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the concept of human rights in an Islamic perspective by exploring the primary sources of the Qur’an and Hadith. This study examines how Islam’s views on human nature, the role of the caliph, and the purpose of human creation affect the understanding of human rights. In addition, this study also analyzes how these concepts are elaborated by scholars and how their implications for human life practices. Through a qualitative approach with literature review, this research is expected to contribute to enriching the understanding of human rights in the context of Islamic values, as well as identifying the relevance of these values in the context of modern life